Completion and adherence rates to exercise interventions in intermittent claudication: Traditional exercise versus alternative exercise – a systematic review. (October 2019) - Lin, Edward; Nguyen, Cindy H; Thomas, Scott G
Background: Intermittent claudication, defined as fatigue or pain in the legs while walking, is a common symptom in peripheral arterial disease. Although exercise effectively improves function and manages symptoms, adherence rates are not ideal. The high levels of pain experienced in traditional exercise programmes may explain the suboptimal adherence. Alternative modalities of exercise can elicit similar benefits to traditional walking exercise. The purpose of this systematic review was to compare completion and adherence rates of exercise programmes in traditional exercise interventions versus alternative exercise interventions among patients with intermittent claudication. Design: Systematic review. Methods: The electronic databases of Medline, SPORTDiscus and CINAHL were searched from the earliest records to March 2018. Search terms were based on 'peripheral artery disease' and 'exercise'. Studies were included if they involved structured exercise and explicitly reported the number of participants that commenced and completed the programme. Results: The search identified 6814 records based on inclusion criteria. Eighty-four full-text records were reviewed in further detail. Out of the 84 studies, there was a total of 122 separate exercise groups, with 64 groups of 'traditional walking exercise' and 58 groups of 'alternative exercise'. Completion and adherence rates for traditional exercise were 80.8% and 77.6%, respectively. Completion and adherence rates for alternative exercise were 86.6% and 85.5%, respectively. Conclusions: The use of alternative modalities of exercise, which have been proved to be as effective as traditional exercise, may offer a solution to the poor participation and adherence rates to exercise in this population.